Lipoma Arborescens of the Elbow: Case Report - Dilek BADAY,; Meltem ARAS,; Aysel ÇOLAK,; Şükrü Cem HATİPOĞLU,; Özdamar Fuad ÖKEN,; Sumru ÖZEL, (Archives of Rheumatology, 2015)
Lipoma arborescens is a rare, benign articular lesion characterized by villous lipomatous proliferation of the synovium caused by replacement of mature fat cells with subsynovial tissue. Although the knee is the most affected joint, lipoma arborescens has also been observed in other locations such as glenohumeral joint, subdeltoid/bicipital bursae, hip, elbow, wrist, and rarely elbow joints. In this article, we report a rare case of lipoma arborescens at the elbow joint in a 30-year-old female patient with cerebral palsy.